Enhanced production of seed oil with improved fatty acid composition by overexpressing NAD+‐dependent glycerol‐3‐phosphate dehydrogenase in soybean. Issue 6 (18th June 2021) - Zhao, Ying; Cao, Pan; Cui, Yifan; Liu, Dongxu; Li, Jiapeng; Zhao, Yabin; Yang, Siqi; Zhang, Bo; Zhou, Runnan; Sun, Minghao; Guo, Xuetian; Yang, Mingliang; et al.
Abstract: There is growing interest in expanding the production of soybean oils (mainly triacylglycerol, or TAG) to meet rising feed demand and address global energy concerns. We report that a plastid‐localized glycerol‐3‐phosphate dehydrogenase (GPDH), encoded by GmGPDHp1 gene, catalyzes the formation of glycerol‐3‐phosphate (G3P), an obligate substrate required for TAG biosynthesis. Overexpression of GmGPDHp1 increases soybean seed oil content with high levels of unsaturated fatty acids (FAs), especially oleic acid (C18:1), without detectably affecting growth or seed protein content or seed weight. Based on the lipidomic analyses, we found that the increase in G3P content led to an elevated diacylglycerol (DAG) pool, in which the Kennedy pathway‐derived DAG was mostly increased, followed by PC‐derived DAG, thereby promoting the synthesis of TAG containing relatively high proportion of C18:1. The increased G3P levels induced several transcriptional alterations of genes involved in the glycerolipid pathways. In particular, genes encoding the enzymes responsible for de novo glycerolipid synthesis were largely upregulated in the transgenic lines, in‐line with the identified biochemical phenotype. These results reveal a key role for GmGPDHp1 ‐mediated G3P metabolism in enhancing TAG synthesis and demonstrate a strategy to modify the FA compositions of soybean oils for improved nutrition and biofuel. Abstract : Upregulation of glycerol‐3‐phosphate formation induced by overexpression of the glycerol‐3‐phosphate dehydrogenase gene GmGPDHp1 in soybean led to an elevated diacylglycerol pool, in which Kennedy pathway‐derived diacylglycerol increased, thereby promoting the synthesis of triacylglycerol with improved fatty acid composition (high levels of C18:1) for human health and industrial applications.